Olive baboons' (Papio anubis) response towards crowned eagles (Stephanoaetus coronatus) at Lake Manyara National Park - Paciência, Filipa M. D. (Primate Biol, 2017)
In this paper we report on two encounters between olive baboons (Papio anubis) and crowned eagles (Stephanoaetus coronatus) at Lake Manyara National Park, northern Tanzania. During these encounters olive baboons responded by giving alarm calls and all infants and juveniles rushed down from trees seeking cover under bushes or close proximity to adult conspecifics. In one of the events, alarm calls from banded mongoose (Mungos mungo) and rock hyraxes (Procavia capensis) most likely triggered alarm calling of vervet monkeys (Chlorocebus pygerythrus) which in turn prompted baboons to respond with alarm calls as well. In both observations, adult male baboons took the lead in climbing trees, threatening the eagle (staring, yawning, ground slapping) and chasing it away. The reaction of the baboons suggests that crowned eagles pose a threat at least for juvenile baboons at Lake Manyara National Park.